Thursday

April 24, 2014

April 24, 2014

Posted by **Joe Schmo** on Tuesday, October 11, 2011 at 7:02pm.

- Calculus -
**Reiny**, Tuesday, October 11, 2011 at 7:41pmUse the quotient rule

dy/dx = [ (x^2+1)^(1/2) (1) - (x+1)(1/2)(x^2+1)^(-1/2) (2x) ]/(x^2+1)

= (x^2+1)^(-1/2) [ x^2 + 1 - x(x+1)]/(x^2+1)

= (1-x)/(x^2+1)^(3/2)

or

= (1-x)(x^2+1)^(-3/2)

or

= (1-x)/√(x^2+1)^3

**Related Questions**

Calculus - Any help would be much appreciated with the steps involved in each ...

Calculus - Any help would be much appreciated with the steps involved in each ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - Given the function: f(x) = x^2 + 1 / x^2 - 9 a)find y and x ...

Calculus - derivatives - Okay, I want to find the derivative of (x^x)^(x^x)... ...

Calculus - I need to find the second derivative of y=x(x-1)^1/2. I found the ...

calculus - find the second derivative of F(x)=3e^-2x(^2) to find the inflection ...

calculus - Differentiate both sides of the double angle identify sin 2x= 2 sin x...

Calculus - How do I use the product rule to solve these two questions. Much ...